EndoVIPER‐seq for Improved Detection of A‐to‐I Editing Sites in Cellular RNA. Issue 2 (29th May 2020) - Knutson, Steve D.; Heemstra, Jennifer M.
Abstract: Adenosine to‐inosine (A‐to‐I) RNA editing is a conserved post‐transcriptional modification that is critical for a variety of cellular processes. A‐to‐I editing is widespread in nearly all types of RNA, directly imparting significant global changes in cellular function and behavior. Dysfunctional RNA editing is also implicated in a number of diseases, and A‐to‐I editing activity is rapidly becoming an important biomarker for early detection of cancer, immune disorders, and neurodegeneration. While millions of sites have been identified, the biological function of the majority of these sites is unknown, and the regulatory mechanisms for controlling editing activity at individual sites is not well understood. Robust detection and mapping of A‐to‐I editing activity throughout the transcriptome is vital for understanding these properties and how editing affects cellular behavior. However, accurately identifying A‐to‐I editing sites is challenging because of inherent sampling errors present in RNA‐seq. We recently developed E ndonuclease V i mmunop recipitation e nr ichment sequencing (EndoVIPER‐seq) to directly address this challenge by enrichment of A‐to‐I edited RNAs prior to sequencing. This protocol outlines how to process cellular RNA, enrich for A‐to‐I edited transcripts with EndoVIPER pulldown, and prepare libraries suitable for generating RNA‐seq data. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : mRNA fragmentation and glyoxalation Basic Protocol 2 : EndoVIPER pulldown Basic Protocol 3 : RNA‐seq library preparation and data analysis